Victims of Robbery with the Forced Defence (Noodweer): A Legal and Victimological Aspects - Rizkyta, Amelia Putri; Holish, Amarru Muftie (Law Research Review Quarterly, 2023)
This study aims to analyze criminal arrangements in the case of victims of violent crimes who then defended forced to exceed the limit due to coercion. This research is normative legal research through a conceptual approach. The results of this study show that victims of violent crimes who commit criminal acts as a defense effort are forced to be free from crime if they meet the requirements based on Articles 48-51 of the Criminal Code. Article 5 Paragraph (1) of Law Number 13 of 2006 concerning the Protection of Witnesses and Victims also explains that victims have the right to protection and a sense of security if there is a gross violation of human rights. However, to get this right, victims still have to go through the legal process.